1997
DOI: 10.1116/1.580653
|View full text |Cite
|
Sign up to set email alerts
|

Improved current–voltage characteristics of downstream plasma enhanced chemical vapor deposition SiNx deposited at low temperature by using He as a dilution gas

Abstract: We have compared the current–voltage characteristics of silicon nitrides prepared from the two gas combinations N2/NH3/SiH4 (N2–SiNx) and He/NH3/SiH4 (He–SiNx) at temperatures between 100 and 350 °C. A downstream plasma enhanced chemical vapor deposition reactor with a non-ECR microwave plasma source has been used. While N2–SiNx with reasonable electrical properties requires deposition temperatures of about 350 °C, the characteristics of He–SiNx even improve at decreasing process temperatures. Almost identical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 17 publications
(23 reference statements)
0
6
0
Order By: Relevance
“…At a temperature of 100 • C, the breakdown field can be enhanced from 4.3 MV/cm to 11.3 MV/cm by using He as a dilution gas. [20]…”
Section: Resultsmentioning
confidence: 99%
“…At a temperature of 100 • C, the breakdown field can be enhanced from 4.3 MV/cm to 11.3 MV/cm by using He as a dilution gas. [20]…”
Section: Resultsmentioning
confidence: 99%
“…the fabrication method does not require high temperature processing. In addition, the Al 2 O 3 films are found to have higher density (3.1 g/cm 3 [8]) than that of plasma-enhanced chemical vapor deposited (PECVD) Si 3 N 4 (2.5 g/cm 3 [9]) which is typically used as the passivation layer for the microelectrodes [10].…”
Section: Methodsmentioning
confidence: 99%
“…Alumina is deposited at the rate of 3 Å/s until the resulting film thickness of 720 -800 nm is obtained. After the photoresist lift-off process, the substrate is then annealed in air at 300°C for 4 h in order to reduce the density of interfacial traps, thus increase the packing density of the alumina sheath for better insulating properties [9,12]. Fig.…”
Section: Methodsmentioning
confidence: 99%
“…It is revealed that the in situ SiN x exhibits a typical silicon nitride behavior. [20][21][22] The curve can be fitted accurately by the combination of an Ohmic conduction mechanism and a Frenkel-Poole emission mechanism, described by…”
mentioning
confidence: 99%
“…The Si-rich in situ SiN x in this study contained relatively high concentrations of Si dangling bonds and distorted excess Si-Si bonds, which may result in midgap defect states or bulk traps inducing more electrical conduction by Frenkel-Poole emission. 20,21 Thus, the resistivity and breakdown field can be further improved by optimizing in situ SiN x growth conditions by MOCVD, such as temperature, pressure, and the gas flow of silane and ammonia, by adjusting the N/Si ratio. the presence of a high quality interface between the in situ SiN x layer and the AlN/GaN heterostructure.…”
mentioning
confidence: 99%